Predictors of Handgrip Strength Among the Free Living Elderly in Rural Pahang, Malaysia - KW Kee; EWH Chang; FM Moy (Tehran University of Medical Sciences, 2011)
Background: Reduced handgrip strength is an aging process that significantly influences the living activities of elderly. It is linked to premature mortality, disability and other health complications among elderly. Therefore, we aim to determine the associated predictors with handgrip strength among the free living elderly in Malaysia. Methods: This was a cross sectional study conducted in a rural state in Malaysia. A total of 434 elderly individuals performed handgrip assessment. Socio-demographic characteristics, medical conditions, occupational history, functional ability (ADL) and depression (GDS) were enquired. Anthropometric measurements (weight and height) were also obtained.Results: Majority of the respondents were Malays with mean age of 67.9 + 6.3 years. Maximum handgrip strength of males and females were 28.8+9.2 kg and 18.9+6.9 kg respectively (P<0.05). The aborigines had significantly lower handgrip strength (P<0.05) compared to Malays, Chinese and Indians. Handgrip strength was positively correlated (P<0.05) with weight, height and ADL, while negatively associated (P<0.05) with GDS for both gender. In the multivariate linear regression analysis; weight, height and race significantly predicted handgrip strength among both male and female elderly after adjustment for all potential confounders. However, GDS and ADL were only found to significantly predict handgrip strength among the male elderly; while age was only significant among the females. Conclusion: Our sample population has significantly lower handgrip strength than the Western counterpart. Weight, height and race significantly predict handgrip strength among both male and female elderly. GDS, ADL are only found to be significant in males while age was only significant among the females.